THE ROLE OF THE FLAG OF UZBEKISTAN IN FOREIGN POLICY - Tuxtayev , Azamat Azizovich; Murodullayev , Malikshokh (Educational Research in Universal Sciences, 2023)
This article delves into the significant and often understated role played by the flag of Uzbekistan in shaping and projecting the country’s foreign policy. The national flag, with its unique design and symbolic elements, serves as a powerful tool in diplomacy, communicating the values, aspirations, and identity of Uzbekistan to the global community. Through a detailed exploration of the historical context, design elements, and instances of the flags utilization in diplomatic events, this article aims to highlight the pivotal role the national flag plays in fostering international relations and contributing to Uzbekistan’s global presence.